2021
DOI: 10.1186/s13567-021-00929-7
|View full text |Cite
|
Sign up to set email alerts
|

Classical scrapie in small ruminants is caused by at least four different prion strains

Abstract: The diversity of goat scrapie strains in Europe has recently been studied using bioassays in a wide collection of rodent models, resulting in the classification of classical scrapie into four different categories. However, the sole use of the first passage does not lead to isolate adaptation and identification of the strains involved and might therefore lead to misclassification of some scrapie isolates. Therefore, this work reports the complete transmission study of a wide collection of goat transmissible spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Molecular investigations and bioassays in rodent models allowed to establish that at least four different strains of classical scrapie do exist [48][49][50]. As regard the prion involved in the Tunisian scrapie case, its molecular signature was typical of classical scrapie and different from both BSE and atypical scrapie.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular investigations and bioassays in rodent models allowed to establish that at least four different strains of classical scrapie do exist [48][49][50]. As regard the prion involved in the Tunisian scrapie case, its molecular signature was typical of classical scrapie and different from both BSE and atypical scrapie.…”
Section: Resultsmentioning
confidence: 99%
“…Classical and atypical scrapie differ in their pathogenesis and transmission. Classical scrapie affects goats and sheep from 2 to 5 years of age, and its infectious nature is well known; it is a highly heterogeneous disease as it can be caused by several different prion strains [15]. On the other hand, atypical scrapie is caused by a single strain (Nor98), which usually affects goats and sheep older than 5 years; atypical scrapie cases seem to be sporadic in nature, although several studies have demonstrated the infectious character of this strain [15][16][17].…”
Section: Scrapiementioning
confidence: 99%
“…Previous strain typing studies in transgenic mice have identified at least five prion strains responsible for classical scrapie [ 19 , 30 , 31 ], but the exact number is unknown and most field isolates even contain sub-strains at different proportions [ 29 , 32 ]. Evidently, some isolates are not completely stable and different replication environments might play an important role in defining their biological properties, which can shift on transmission and even affect the ability of certain strains to cross the species barrier [ 19 ], as was shown for some classical scrapie isolates in humanized transgenic mice [ 33 ].…”
Section: Introductionmentioning
confidence: 99%